Les usages des cartes dans le tournant papier / écran : analyse des préférences informationnelles et typologie d’utilisateurs - Quentin Morcrette (Netcom)
Information and communication technologies deeply transform the nature of maps ; screen reading not only modifies map content but also the way individuals perceive it and use it. Yet, despite the significance of this change, paper maps have not disappeared, and a coexistence of the two types of map media seems to characterize the current period. This paper discusses the different uses and perception of paper and digital maps by confronting the answers of two panels of expert users, in France and in the United States. Two different points are studied, from a quantitative perspective. One broad-based analysis questions the advantages and qualities that participants assign to the different maps according to the medium. A second and more specific aspect deals with the uses and preferences of the respondents when maps are used for mobility. The results of the study show that qualities credited to cartographic representations vary depending on the medium considered and that users’ preferences are correlated with their digital practices.